The Agreement Compatibility Level of Tuberculin Skin Test (TST) and POT.TB in Detecting Latent Tuberculosis Infection (LTBI) in Diabetic Mellitus (DM) - Sebayang, Pribadi M; Reviono, Reviono; Kartodarsono, Supriyanto (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: The lifetime risk of TB reactivation develops within the first 5 years after initial infection. Good LTBI management helps in preventing the progression of the disease to be active. It is recommended in countries with a low prevalence of TB infection and high risk populations such as DM patients. The diagnosis of LTBI is done by examining TST and T-SPOT.TB. This study aimed to determine the correspondence between TST and T-SPOT.TB in detecting LTBI in DM patients. Methods: This cross-sectional study was conducted in DM patients treated in Dr. Moewardi Hospital Surakarta in September 2018. The study subjects received TST by injecting intradermal PPD RT 23 2TU intradermally, and T-SPOT.TB by taking 6 ml of venous blood examined with ELISPOT method. Statistical analysis used SPSS21 for windows. Results: There were 30 subjects. The prevalence of LTBI was 20%. The correspondence between TST and T-SPOT.TB was substantial (K=0.667, p